An Energy-Efficient Key Management Scheme using Trust Model for Wireless Sensor Network - P. Raja; E. Karthikeyan (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
In wireless sensor networks (WSNs), secret shared keys must be established with the neighboring nodes in order to achieve secure communication. The challenge issues for secured communication in WSN are the Key management. Location Dependent Key (LDK) management is a suitable scheme when compared to other location based key management schemes because of lesser memory space requirement and lesser number of keys to be stored on each sensor node. However, the LDK is affected by communication interference problem which is solved by the key is distributed based on trust model. The distributed key updates and revocation processes are effectively resist inside attackers. An energy-efficient Key Management with Trust Model (KM-TM) for WSNs is proposed to achieve the secured communication and the nodes are resisting from the attackers. The performances of proposed KM-TM for WSNs are evaluated in terms of trustworthiness of sensor nodes and security breaches more effectively.